In Situ Scanning Electron Microscope Observations of Li Plating/Stripping Reactions with Pt Current Collectors on LiPON Electrolyte. Issue 7 (1st January 2018) - Motoyama, Munekazu; Ejiri, Makoto; Yamamoto, Takayuki; Iriyama, Yasutoshi
Abstract : This paper reports the results of in-situ scanning electron microscope (SEM) observations of Li plating and stripping with Pt current collector (CC) films on lithium phosphorus oxynitride (LiPON) glass electrolyte. Before the Li nucleation, Li-Pt alloying reactions occur while the voltage shows positive values. Li nucleates and starts to grow after the voltage decreases, which shows the lowest value in the negative voltage region. After Li-supersaturated-Pt surfaces are locally deformed into dome shapes where Li particles grow underneath, a hole opens in the center of each dome. This is a different CC fracture mechanism from that of non-alloying-CC films such as Cu. This difference in fracture mechanism is derived from a supersaturation process of Pt with Li, which plays a critical role in achieving smaller nucleation overpotentials and larger nucleation number densities compared to the case with Cu.